Cross-Cultural Reflections on Citizen’s and Mankind’s Moral Identity as a Foundation of Community with a Shared Future - Yang , Shaogang (ETHICS IN PROGRESS, 2022)
Citizens’ moral identity is not only reflected on the individual level, but also in terms of belongingness, community, and even cosmopolitanism. It is the basic demand of a community with a shared future in morality. Moral identity is closely related to moral behavior, and the study of moral identity can predict one’s moral behavior. Community is the cultural basis of citizens’ moral identity. To study citizens’ moral identity in the community can also enable one to predict people’s moral behavior in that community. At present, the construction of a community with a shared future still lacks a species moral identity generally recognized by all cultures and countries. In order to achieve that goal, we must strengthen cultural inclusion, advocate and practice species moral identity of a community with a shared future. Species moral identity is based on the existence of humankind as a species with autonomous identity, so it is necessary to establish the mechanism of cultural respect and equal discussion, and to strengthen the construction of the species moral identity. Only in that way can we accomplish the mission of establishing species moral identity. In the following paper, I will advocate for these ideas with Kant’s and Marx’ thoughts.